PENGARUH LEVERAGE DAN RASIO LIKUIDITAS TERHADAP NILAI PERUSAHAAN: (Studi Kasus pada Perusahaan Sektor Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2011 s/d 2016) - Ike Riwayati Ningsih; Sigit Mulyanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2018)
This research was conducted to determine the effect of leverage, liquidity ratio on company value. The sample consisted of 58 companies with purposive sampling method on manufacturing companies in the Indonesia Stock Exchange. The dependent variable in this study was the value of the company measured using the tobin’sQ formula. There are two control variables in this study namely, Company Size and Ylag1. The results of this study, namely leverage (DAR) has a negative and insignificant effect on the value of the company. The liquidity ratio (CR) has a positive and insignificant effect on the value of the company. Taken together leverage and liquidity ratios have a positive effect on firm value. In addition, Ylag1 control variables have a positive and significant effect on firm value, and the size of the company has a positive and insignificant effect on the value of the company